2004
DOI: 10.1207/s15327914nc4802_5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Pharmacokinetics of Purified Soy Isoflavones: Multiple-Dose Administration to Men with Prostate Neoplasia

Abstract: A phase I clinical trial was conducted to determine the safety, pharmacokinetic parameters, and efficacy of orally administered isoflavones (genistein and daidzein, potential cancer chemotherapeutic agents) over a 3-mo period in men with prostate neoplasia. Twenty men, ages 40 and above, with stage B, C, or D adenocarcinoma of the prostate were treated with a multiple-dose regimen of a soy isoflavone formulation (delivering approximately 300 or 600 mg/day genistein and half this much daidzein) for 84 days. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 33 publications
4
56
0
1
Order By: Relevance
“…Soy was also not effective in reducing PSA levels in a phase I clinical trial to determine the safety of high-dose oral isoflavones in 20 men with prostate cancer. 31 Fischer et al 31 gave subjects with stage B, C or D prostate cancer a multiple-dose regimen of a soy isoflavone formulation (delivering approximately 300 or 600 mg/day genistein and half this much daidzein) for 84 days. Seven patients were excluded from the analysis of PSA values because the respective PSA was undetectable or o0.4 ng/ml.…”
Section: Clinical Effects Of Soy In Humansmentioning
confidence: 99%
“…Soy was also not effective in reducing PSA levels in a phase I clinical trial to determine the safety of high-dose oral isoflavones in 20 men with prostate cancer. 31 Fischer et al 31 gave subjects with stage B, C or D prostate cancer a multiple-dose regimen of a soy isoflavone formulation (delivering approximately 300 or 600 mg/day genistein and half this much daidzein) for 84 days. Seven patients were excluded from the analysis of PSA values because the respective PSA was undetectable or o0.4 ng/ml.…”
Section: Clinical Effects Of Soy In Humansmentioning
confidence: 99%
“…(Akiyama et al, 1987) c. (Sallman et al, 2007) d. (Dorai et al, (Bemis et al, 2004;Li & Sarkar, 2002;El Touny & Banerjee, 2007;Park et al, 2005) b. (Ivanov et al, 2007) c. (Aziz et al, 2006;Chen et al, 2010) d. (Yu et al, 2008; pharmacokinetic study (Fischer et al, 2004), though serum dehydroepiandrosterone was reduced by 31.7% (P = 0.0004) at the end of the study, and estrogenic side effects were encountered. Biologically relevant concentrations of genistein, commensurate with in vitro activity, can be achieved with high doses of genistein -enriched isoflavone extracts (Takimoto et al, 2003).…”
Section: Clinical Studies In Prostate Cancermentioning
confidence: 97%
“…Pharmacokinetic studies have shown that genistein has very long half-life (46 h) after oral administration and that different dose of genistein show no correlation of AUC, suggesting that there may be unknown mechanism of elimination and recycling system [135,136]. In human, genistein is extensively metabolized and the plasma level of unconjugated form is very low [137,138]. Several human clinical pharmacokinetic studies have revealed that the level of total genistein in plasma is within micro molar range while the genistein aglycone, a biological active form compared to genistein conjugates, is in hundred nano molar range [138,139].…”
Section: Bioavailability Safety Tolerability and Pharmacokineticsmentioning
confidence: 99%
“…In human, genistein is extensively metabolized and the plasma level of unconjugated form is very low [137,138]. Several human clinical pharmacokinetic studies have revealed that the level of total genistein in plasma is within micro molar range while the genistein aglycone, a biological active form compared to genistein conjugates, is in hundred nano molar range [138,139]. There were adverse events in a clinical trial using genistein 30 mg/day for 6 weeks, but all events, including gastrointestinal and cardiovascular, were mild and no patients aborted the protocol due to the events [134].…”
Section: Bioavailability Safety Tolerability and Pharmacokineticsmentioning
confidence: 99%